USABILITY ANALYSIS ON THE ENDANGERED INDONESIAN ANIMALS AND PLANTS AUGMENTED REALITY APPLICATION - Putri Syifa Darmawel (Jurnal Techno Nusa Mandiri, 2020)
Knowledge about Indonesian endangered animals and plants has been taught at elementary school, but still based on text. In curriculum 2013, teachers are expected to be able to develop creative ideas such as using interactive learning media that makes learning fun for students. Interactive learning media can be used as a solution to make learning process more interesting. The use of augmented reality technology can be implemented on interactive learning media that aims to increasing elementary school children interest and make the learning process easier to teacher. This research uses descriptive quantitative method by distributing questionnaires to test HEBULA Application which is an interactive learning media for introducing endangered Indonesian animals and plants using augmented reality technology for elementary school children. Testing is done by using User Acceptance Test (UAT). This research aims to find out weather the HEBULA Application can be well receive and effectively used as a learning media. The results of this research show that HEBULA Application is suitable to be used as a learning media which is shown by the percentage of UAT eligibility of 92,6% that can be categorized as very well.